The effect of BCG vaccination on macrophage phenotype in a mouse model of intranasal Mycobacterium bovis challenge. Issue 30 (19th June 2020) - Civello, Alexander N.; Spiropoulos, John; Sánchez-Cordón, Pedro J.; Hicks, Daniel J.; Hogarth, Philip J.; Birch, Colin; Núñez, Alejandro
Highlights: The effect of BALB/c mice vaccination with BCG on macrophage phenotype was evaluated. Vaccinated mice shown a reduced bacterial lung burden regarding control mice. Vaccinated mice displayed a significant decrease in Arg1+ macrophages in lung. The decrease in Arg1+ macrophages may be caused by Th1 polarization. Abstract: In order to develop improved vaccinations against tuberculosis, it is essential to understand the effect of vaccination on the immune response, and to overcome the mechanisms by which mycobacteria regulate this immune response. In this study, we examine the effect of intradermal vaccination with Mycobacterium bovis bacille Calmette-Guèrin on macrophage phenotype following intranasal challenge with virulent Mycobacterium bovis . Preserved lung tissues used in the present study were obtained from a previous vaccination trial in BALB/c mice. Vaccinated mice showed less extensive pulmonary lesions along with a significant decrease in bacterial lung burden when compared to control mice. Immunohistochemical markers of classically activated macrophages (iNOS) and alternatively activated macrophages (Arg1, FIZZ1) were applied to lung sections. Vaccination led to a statistically significant decrease in the number of Arg1+ macrophages. The presence of macrophages that expressed Arginase 1 in pulmonary lesions was much smaller than the presence of macrophages expressing iNOS. The low presence of Arg1+ macrophages induced by vaccination may be caused by Th1 polarization and may reduce alternative activation of macrophages, with an overall more effective intracellular killing of bacteria.